Perspectives of Nunavut patients and families on their cancer and end of life care experiences. Issue 1 (1st January 2020) - Galloway, Tracey; Horlick, Sidney; Cherba, Maria; Cole, Madeleine; Woodgate, Roberta L; Healey Akearok, Gwen
ABSTRACT: The present study arose from a recognition among service providers that Nunavut patients and families could be better supported during their care journeys by improved understanding of people's experiences of the health-care system. Using a summative approach to content analysis informed by the Piliriqatigiinniq Model for Community Health Research, we conducted in-depth interviews with 10 patients and family members living in Nunavut communities who experienced cancer or end of life care. Results included the following themes: difficulties associated with extensive medical travel; preference for care within the community and for family involvement in care; challenges with communication; challenges with culturally appropriate care; and the value of service providers with strong ties to the community. These themes emphasise the importance of health service capacity building in Nunavut with emphasis on Inuit language and cultural knowledge. They also underscore efforts to improve the quality and consistency of communication among health service providers working in both community and southern referral settings and between service providers and the patients and families they serve.